Erythrocyte Membrane Protein 3 (EMAP3) Is Exposed on the Surface of the Plasmodium berghei Infected Red Blood Cell - Hernandez, Sophia Raine C. (2026)
The human malaria parasite Plasmodium falciparum invades red blood cells (RBCs) and exports parasite proteins to transform the host cell for its survival. These exported proteins facilitate cytoadherence of the infected RBC (iRBC) to endothelial cells of small blood vessels, protecting iRBCs from splenic clearance. The parasite protein PfEMP1 and the host protein CD36 play a major role in P. falciparum iRBC cytoadherence. The murine parasite Plasmodium berghei is a widely used experimental model that combines high genetic tractability with access to in vivo studies. The P. berghei iRBC also sequesters by CD36-binding via an unknown parasite ligand and few parasite proteins, including EMAP1 and EMAP2, have been localised to the iRBC membrane. We have identified a new protein named EMAP3 and demonstrated its export to the iRBC membrane where it likely interacts with EMAP1, with only EMAP3 exposed on the outer surface of the iRBC. Parasites lacking EMAP3 display no significant reduction in growth or sequestration, indicating that EMAP3 is not a major CD36-binding protein. The outer-surface location of EMAP3 offers a new scaffold for displaying P. falciparum proteins on the surface of the P. berghei iRBC, providing a platform to screen in vivo for putative inhibitors of P. falciparum cytoadherence.